PENGARUH PROFITABILITAS, MARKET RATIO DAN SOLVABILITAS TERHADAP HARGA SAHAM DI PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2021-2024 - Chionia Angel Yulana; I Gede Agus Pertama Yudantara; I Putu Gede Diatmika (Vokasi : Jurnal Riset Akuntansi, 2026)
The purpose of this research is to analyze the influence of profitability, market ratio, and solvency on stock prices in companies that are members of the LQ45 index on the Indonesia Stock Exchange for the 2021–2024 period. This research is motivated by the phenomenon of stock price fluctuations that do not always reflect the fundamental condition of the company in the midst of high market volatility. The independent variables used are profitability proxied by Return on Assets (ROA), market ratio with Price to Book Value (PBV), and solvency with Debt to Equity Ratio (DER), while dependent variables are stock prices. This study uses a quantitative approach with secondary data obtained from financial statements and stock price data. The sampling technique uses purposive sampling with the criteria of companies that are consistently listed in the LQ45 index. The analysis method used is multiple linear regression. The results of the study show that the profitability variable has a positive effect on the stock price, while the market ratio and solvency have a negative effect on the stock price.